MoDELS 2007 Doctoral Symposium summary - Sin autor (2007)
The MoDELS 2007 Doctoral Symposium provided a forum for Ph.D. students, conducting research in model-driven software engineering, to discuss their goals, methodology and results at an early stage in their research, in a critical but supportive and constructive environment. The symposium offered an opportunity for the eight student participants to interact with other students at a similar stage in their careers and with the mentoring board composed of five experts in the software modeling field. The students received practical guidance for the completion of the dissertation research and motivation for a research career. This summary offers an overview of the activities that occurred at the Symposium.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática-UNLP (Colección BIPA / Biblioteca.) -- Disponible también en línea (Cons. 09/03/2009)
Proceedings of the Doctoral Symposium at the ACM/IEEE 10th International Conference on Model-Driven Engineering Languages and Systems, Nashville (TN), USA, October 1st, 2007. CEUR Workshop Proceedings, ISSN 1613-0073, Vol.262. 2007. -- Lecture Notes in Computer Science (LNCS), volume on Models in Software Engineering: Workshops and Symposia at MoDELS 2007. Springer-Verlag, Berlin Heidelberg. ISSN 0302-9743. 2008.
Keywords: INGENIERÍA DE SOFTWARE DIRIGIDA POR MODELOS - MDE